Relevance of ERK1/2 Post-retrieval Participation on Memory Processes: Insights in Their Particular Role on Reconsolidation and Persistence of Memories - Krawczyk, Maria C.; Millan, Julieta; Blake, Mariano G.; Feld, Mariana; Boccia, Mariano M. (Frontiers in Molecular Neuroscience, 2019)
Back in 1968, Misanin and his group posited that reactivation of consolidated memories could support changes in that trace, similar to what might happen during consolidation process. Not until 2000, when Nader and collaborators studied the behavioral effect of a protein synthesis inhibitor on retrieved memories, could this previous statement be taken under consideration once again; suggesting that consolidated memories can become labile after reactivation (Nader et al., 2000). The process of strengthening after memory labilization was named memory reconsolidation. In recent years, many studies pointed towards a critical participation of the ERK/MAPKs pathway in different memory processes (e.g. consolidation, extinction, reconsolidation, among others). In this review, we will focus on how this system might be modulating the processes triggered after retrieval of well-consolidated memories in mice.